The lived experiences of youth residing in Elias Motsoaledi Municipality at Sekhukhune District about Nyaope - Mamukeyani, Eric (My University, 2021)
The purpose of this study was to determine and describe the lived experiences of youth residing in Elias Motsoaledi Municipality at Sekhukhune District about Nyaope. A qualitative research was applied using the Phenomenolgical research design to explore the lived experiences. The purposive sampling technique was used to select the participants at Rite Substance organization between the age of 18 and 35, and also the convenient sampling applied to select key informants. The study revealed that the youth Nyaope users experienced; the lived physical effects such as ;bodily weakness and strenght, bodily pains, drowsiness, loss of appetite and poor hygiene, the psychological effects such as mental relaxation, regret and worry, drug dependency and addiction, and the social effects such as family rejection, community stigmatization, relationship failure, engagement in crime, and economic and educational failure. As such, more funds, staff and resources are needed to assist in dealing with the Nyaope crisis.
Thesis (MPH.) -- University of Limpopo, 2021
Keywords: Nyaope; Youth; illicit; Psychoactive; Substance abuse; Substance abuse; Drug abuse -- Social aspects -- South Africa -- Limpopo; Substance abuse -- South Africa -- Limpopo; Youth -- South Africa -- Social conditions